Effect of Cooling Rate on Microstructure and Properties of Twin-Roll Casting 6061 Aluminum Alloy Sheet - Zhen Xu; Sixue Wang; Hongbin Wang; Hua Song; Shengli Li; Xingyu Chen (Metals, 2020)
In this study, a twin-roll casting sheet of 6061 aluminum alloy was cooled using furnace, asbestos, air, wind and water. The effect of cooling rate on the microstructure and properties of twin-roll casting 6061 aluminum alloy sheet were studied. Optical microscope, scanning electron microscope, X-ray diffraction, microhardness tester and universal tensile machine were used to observe the microstructure and properties of twin-roll casting sheet of 6061 aluminum alloy. The results show that the higher the cooling rate, the smaller the grain size of the alloy and the smaller the number of precipitated phases in the matrix. Uniform grain size of the alloy could be obtained at a stable cooling rate. The hardness, tensile strength and elongation of the twin-roll casting sheet increased with cooling rate. Under wind cooling condition, the twin-roll casting sheet demonstrated excellent comprehensive performance, i.e., 88 MPa of yield strength, 178 MPa of tensile strength and 15% of elongation, respectively. A quantitative Hall–Petch relation was established to predict the yield strength of 6061 twin-roll casting sheets with different grain sizes and cooling rate.